Mediterranean diet and the risk of poor semen quality: cross‐sectional analysis of men referring to an Italian Fertility Clinic. (20th January 2019) - Ricci, E.; Bravi, F.; Noli, S.; Ferrari, S.; De Cosmi, V.; La Vecchia, I.; Cavadini, M.; La Vecchia, C.; Parazzini, F.
Abstract: Background: Several diet patterns have been suggested as involved in processes of spermatogenesis and thus in male subfertility. To study the relation between Mediterranean diet and abnormal sperm parameters in men of subfertile couples, we performed a cross‐sectional analysis of baseline data from a prospective cohort study. Methods: Patients were enrolled in an Italian Fertility Clinic. Couples undergoing assisted reproduction techniques (ART) were interviewed to obtain information on personal and health history, lifestyle habits, and diet, on the day of oocyte retrieval. On the same day, a semen sample was also collected and analyzed to proceed with ART. Adherence to Mediterranean diet was evaluated using a Mediterranean Diet Score (MDS). Odds ratios (OR) and 95% confidence intervals (CI) were calculated for semen volume <1.5 mL, sperm concentration <15 mil/mL, and total count <39 mil. Results: Three hundred nine men, age range 27–60, were enrolled: 19.3% had semen volume < 1.5 mL, 30.5% sperm concentration <15 mil/mL, and 32.1% total count <39 mil. MDS was low (0–3) in 86 men (27.8%), intermediate (4–5) in 131 (42.4%), and high (6–9) in 92 (29.8%). Semen volume was not associated with MDS. Compared to the highest MDS category (6–9), the ORs for low sperm concentration were 1.34 (95% CI 0.69–2.50) for MDS 4–5 and 2.42 (95% CI 1.21–4.83) for MDS 0–3, with significant trend ( p = 0.011). The corresponding estimates for total count were 1.26 (95% CI 0.66–2.42) and 2.08 (95% CI 1.05–4.12), with significant trend ( p = 0.034). These findings were consistent in strata of history of reproductive organ diseases. Conclusions: Mediterranean Diet Score was positively associated with normal sperm concentration and total count, but not with semen volume.